Band of sisters : a novel - Willig, Lauren (William Morrow, an imprint of HarperCollinsPublishers, 2021)
Eschewed by her wealthy Smith College classmates, a former scholarship student reluctantly volunteers to join a group of graduates who travel to Europe to help World War I French civilians before finding herself surrounded by desperate families in villages decimated by German bombs.